Intraintestinal and Parenteral Administration of an Insulin Analogue Leads to Comparable Activation of Signaling Downstream of the Insulin Receptor in the Small Intestine. (January 2020) - Hvid, Henning; Kildegaard, Jonas; Kristensen, Kim; Porsgaard, Trine; Jørgensen, Mikkel S.; Ballarín-González, Borja; Ahnfelt-Rønne, Jonas; Hansen, Bo F.; Nishimura, Erica
Background: Oral delivery of insulin was recently demonstrated to have therapeutic relevance in patients with diabetes. Insulin receptors are expressed in the gastrointestinal tract and can be activated by insulin in the bloodstream, but it is not known if the large amount of insulin in the intestinal lumen required for sufficient oral delivery will induce a different effect. The aim of this study was to compare the acute effect in the intestine of insulin administered in the intestinal lumen with that of insulin administered by a parenteral route. Method: Intraintestinal (ii) injection in the mid-jejunum of anaesthetized rats with insulin analogue 106 (I106), formulated with the absorption-enhancer sodium caprate, was used as an animal model of oral insulin administration. As control treatment, rats were treated with I106 by iv infusion according to algorithms which precisely mimicked the pharmacokinetic and pharmacodynamic properties of ii administered I106. Several fold more I106 was administered by ii injection than by iv infusion. Phosphorylated Akt (Ser473) was used as indicator of insulin-stimulated acute effects in the intestine. Results: Treatment with I106 resulted in activation of Akt in the intestine, with no significant difference between the effects of ii or iv administration. Conclusion: The results from this rat model of orally administered insulin indicate that the unabsorbed insulin in the intestinal lumen after oral administration will not result in an enhanced acute effect in the intestine.